Using Cover Crops to Control Weeds and Improve Soil Health - J. Dille; A. Hewitt; G. Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2022)
Herbicide-resistant weeds are challenging for producers to control in crop fields. This study explores the potential of cover crops to reduce weed pressure and improve soil health. Cover crops that had good canopy development, including grasses such as ryegrass and wheat, had the best weed control. Soybean yields were similar for all cover crops, though there was a trend towards lower yields for the brassica cover crops, Graza radish and forage collards. Soybeans grown after ryegrass had the highest yields.
Keywords: cover crops; weed management; soil health; weed control; soybean yield